The Influence of Contextual Teaching and Learning Model on Science Learning Outcomes in Elementary School - Jihan Nur Afifah; Mustamiroh Mustamiroh; Kusdar Kusdar (Edumaspul: Jurnal Pendidikan, 2023)
Abstract This study aims to determine: 1) differences in science learning outcomes in the experimental class and control class, 2) differences between the pretest and posttest using the Contextual Teaching and Learning learning model, and 3) the effect of using the Contextual Teaching and Learning learning model on science learning outcomes. This type of research is a quantitative experimental research method with the True Experimental Pretest-Posttest Control Group Design model. The results showed that the science learning outcomes between the experimental class and the control class from the results of the t-test calculation obtained the mean value for the experimental class was 73,63 and for the control class was 67,88 with a mean difference of 5,750 and ρ < 0,05 (0,017 < 0,05) then Ho is rejected. The results of data analysis before the experiment was carried out the average science learning result was 64,50 and after the experiment it was 82,75 with ρ < 0,05 (0,000 < 0,05) then Ho was rejected. Thus it can be concluded that there is an effect of using the Contextual Teaching and Learning learning model on science learning outcomes in class IV students at SD Negeri 016 Sungai Kunjang.